If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + 7) = -46 + 30 Reorder the terms: 2(7 + 5x) = -46 + 30 (7 * 2 + 5x * 2) = -46 + 30 (14 + 10x) = -46 + 30 Combine like terms: -46 + 30 = -16 14 + 10x = -16 Solving 14 + 10x = -16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 10x = -16 + -14 Combine like terms: 14 + -14 = 0 0 + 10x = -16 + -14 10x = -16 + -14 Combine like terms: -16 + -14 = -30 10x = -30 Divide each side by '10'. x = -3 Simplifying x = -3
| y=4x^2+60x+224 | | 5x+6x-2=0 | | X=-0.5t^2+3t+2 | | 10x+9x=12 | | a^4b/a^2b | | 6b+8=5b+1 | | 4+b/3=11 | | (e^4x+1)-3=8 | | 0=-16t^2+60t+3 | | 76.06x+221.52y=84318.84 | | y^2-27-66=0 | | x^2+20x=-100 | | 0=-16t^2+24t+7 | | 4b+5=2 | | 8+34x=-60forx | | 36500(1+0.090/4)4*18 | | X^3-X=3 | | c-7=11 | | 5x+10=10+2x | | 12n^8+12n^7+n^6/6n | | 4x+8=-2x-34 | | 6-2x+4x=10 | | 7y+8=-2-64 | | -1=3x-2x-4 | | -4x+1/4(12+8x)=-4 | | (x^3)-8x+3=7 | | x^3-8x+3=7 | | -9.60+0.85c/-0.50 | | x^2+10x+25=-3 | | -18v^3z^6+27v^5z^6/3v^4z^5 | | 95-4x=2x | | (3x+1)+50=180 |